1995
DOI: 10.1007/bf00198312
|View full text |Cite
|
Sign up to set email alerts
|

Influence of renal function on the steady-state pharmacokinetics of the antiarrhythmic propafenone and its Phase I and Phase II metabolites

Abstract: The aim of this study was to investigate the disposition of propafenone and its Phase I and II metabolites in relation to kidney function under steady-state conditions. The mechanism of the renal handling of propafenone glucuronides (filtration, secretion) was also examined. Racemic (R/S) propafenone was administered to 7 young volunteers, to 5 older patients with a normal glomerular filtration rate and to 4 patients with chronic renal failure. No difference was found in the plasma concentrations of propafenon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…This is not surprising because dextrorphan is excreted in urine as a conjugate of glucuronic acid.24 A recent study with propafenone, which is in part excreted in urine as glucuronides, showed that the renal clearance of propafenone glucuronides decreases with age and even more so in patients with impaired renal function. 25 Thus it is likely that, in our study, the urinary excretion of dextrorphan was largely influenced by renal function because after the formation of dextrorphan by CYP2D6, its glucuronides could not be excreted in our patients with renal failure. We can-not rule out that if dextrorphan had been collected in urine over a longer period of time, better relationships between its fractional excretion and sparteine-based indexes of CYP2D6 activity could have been found.…”
Section: Discussionmentioning
confidence: 66%
“…This is not surprising because dextrorphan is excreted in urine as a conjugate of glucuronic acid.24 A recent study with propafenone, which is in part excreted in urine as glucuronides, showed that the renal clearance of propafenone glucuronides decreases with age and even more so in patients with impaired renal function. 25 Thus it is likely that, in our study, the urinary excretion of dextrorphan was largely influenced by renal function because after the formation of dextrorphan by CYP2D6, its glucuronides could not be excreted in our patients with renal failure. We can-not rule out that if dextrorphan had been collected in urine over a longer period of time, better relationships between its fractional excretion and sparteine-based indexes of CYP2D6 activity could have been found.…”
Section: Discussionmentioning
confidence: 66%
“…It is not known yet whether piceatannol conjugates also exhibit pharmacological activity. However, numerous studies have shown that glucuronides can accumulate during chronic therapy (31–33) . Cleavage of the glucuronides by human ÎČ‐glucuronidase, an enzyme expressed in many tissues and body fluids in humans, can release the parent compounds and thereby modify drug disposition (34) .…”
Section: Discussionmentioning
confidence: 99%
“…Particularly glucuronidation can be a major cause of change in pharmacological activities and pharmacokinetic phenomena. The increased hydrophilicity of glucuronidated metabolites changes the enterohepatic circulation, metabolism in the liver and intestine, as well as renal and biliary excretions of the parent compound and its metabolites, thus modifying the pharmacological activities [17,18]. Thus, the determination of the pharmacokinetic profiles of isoLQ as well as those of its metabolites may make it possible to figure out the substantial function of isoLQ in living organisms.…”
mentioning
confidence: 99%